The Influence Of Work-Life Balance, Work Ethic, And Human Relations On Employee Productivity At The Seluma Regency Education And Culture Office - Marwanto Marwanto; Ida Anggriani; Ida Ayu Made E. Gayatri (Focus of Human Resource Management Journal, 2026)
To achieve optimal productivity, employees must possess knowledge, skills, abilities, and positive behaviors in carrying out their duties. Increasing employee productivity is influenced by several factors, such as work-life balance, work ethic, and human relations. The purpose of this study was to determine the effect of work-life balance, work ethic, and human relations on employee productivity at the Seluma Regency Education and Culture Office. The sample in this study was 81 employees at the Seluma Regency Education and Culture Office who had become civil servants. Data collection used a questionnaire, and the analysis methods used were multiple linear regression, determination tests, and hypothesis testing. The results of the multiple regression test showed a positive trend with the regression equation Y = 5.715 + 0.184X1 + 0.398X2 + 0.306X3 + 3.592. Variable X1 (Work-Life Balance) has a significant effect on Y (Work Productivity), as evidenced by the significance value of 0.036 <0.05. Therefore, it can be concluded that Hypothesis 1 is accepted. Variable X2 (Work Ethic) has a significant effect on Y (work productivity) this can be seen from the significance value of 0.000 <0.05. then it can be concluded that hypothesis 2 is accepted. Variable X3 (human relations) has a significant effect on Y (work productivity) this can be seen from the significance value of 0.001 <0.05, then it can be concluded that hypothesis 3 is accepted. The results of the simultaneous test then H0 is rejected and Ha is accepted, between the independent variables namely X1 (work life balance), X2 (work ethic), X3 (human relations), have a significant effect together on work productivity (Y) because the significance value of 0.000 is small from 0.05.